Die beleid en optrede van die Vrystaatse regering gedurende die Ontwapeningsoorlog in Basoetoland1880-1881 (Historia, 2021)
-
Keywords: Cape Colony; Disarmament; Basutoland; Act for the better preservation of peace within the Colony; Peace Preservation Act; Free State Government; Basutos